1967
DOI: 10.1161/01.res.21.1.99
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Left Ventricular Myocardial Function in the Intact, Sedated Dog

Abstract: Instantaneous contractile element velocity was calculated from left ventricular pressure and its first derivative during isovolumic left ventricular contractions produced by sudden balloon occlusion of the ascending aorta during diastole in closed-chest, sedated dogs. Wall tension was derived from ventricular pressure and volume, the latter being obtained from the pressure-volume relation of the arrested ventricle. During isovolumic contractions, there was an inverse curvilinear relation between tension and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

1968
1968
1987
1987

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 49 publications
3
43
0
1
Order By: Relevance
“…They concluded that aortic valve opening tends to limit max dP/dt. In the present study, max dP/dt of single isovolumic beats was generally identical with that of the preceding auxotonic beat and a similar experience has been reported by others (6,32). It should be noted that in the studies of Wildenthal et al, an air pump was used to elevate aortic pressures and central pulse pressures were unusually wide at the heart rates studied.…”
Section: Introductionsupporting
confidence: 90%
“…They concluded that aortic valve opening tends to limit max dP/dt. In the present study, max dP/dt of single isovolumic beats was generally identical with that of the preceding auxotonic beat and a similar experience has been reported by others (6,32). It should be noted that in the studies of Wildenthal et al, an air pump was used to elevate aortic pressures and central pulse pressures were unusually wide at the heart rates studied.…”
Section: Introductionsupporting
confidence: 90%
“…In the seven patients in whom the effects of supine leg exercise were studied, dp/dt at any pressure throughout the period of isovolumic contraction rose significantly (P < 0.01), while (dp/dt)/CP1P increased strikingly, from 29 ' 9 that although peak ventricular dp/dt is exquisitely sensitive to changes in the inotropic state, it also can be affected to some degree by alterations of arterial diastolic pressure, which is a function of ventricular afterload and, therefore, of the peripheral vascular bed. Unless diastolic pressure is markedly elevated, peak dp/dt usually occurs Relation between left ventricular end-diastolic pressure and left ventricular dp/dt at a commotn level of isovolumetric pressure (40 mm Hg).…”
Section: Exercisementioning
confidence: 93%
“…A spherical model for the left ventricle was utilized, and the calculations were similar to those described previously by others*. 10 (table 1). There were no significant differences in the baseline cardiac outputs between the groups (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…At rest in their cages, heart rate in the stressed animals was 20-30 beats/min faster than in the sham-operated or control dogs. Under the conditions of the experimental dT/ dl is the series elastic constant, numerically equal to 30 T.9 10 When left ventricular peak systolic pressures, peak systolic wall stress, peak dp/dt, and peak contractile element velocity( (VICE) at four matched levels of left ventricular enddiastolic pressure were compared, left ventricular performance appeared to be appreciably depressed (table 2, fig. 2).…”
Section: Methodsmentioning
confidence: 99%